Tittle book: An introduction to qualitative research. Author: Uwe Flick - Castiblanco, Olga; Vizcaino, Diego (Góndola, Enseñanza y Aprendizaje de las Ciencias, 2020)
This book is a good referential guide for both novice and experienced researchers because it gives detailed descriptions of qualitative research and offers information that leads to a deeper understanding of the subject. Additionally, it is noted that the book introduces current issues, including ethics in qualitative research, the use of literature in qualitative research, the relationship between qualitative and quantitative research and qualitative online research, in relation to each topic. In the final chapter, the author proposes the future of qualitative research as a combination of art and method.